THE INFLUENCE OF JOB SATISFACTION ON EMPLOYEES' JOB PERFORMANCE WITH AFFECTIVE COMMITMENT AS MEDIATOR The Case of PT Telkom Kotabaru Yogyakarta - , Lughni Zaid Alfadjri, Gugup Kismono, Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The influence of job satisfaction on job performance was found to be inconsistent, and these inconsistencies have led some researchers to argue that there is a mediator variable in the influence of job satisfaction on job performance. Previous research has found that affective commitment mediates the influence of job satisfaction on job performance. This gives implication to organizations that to improve job performance, they should concern to enhance not only job satisfaction but also affective commitment. The main objective of this research is to analyze the role of affective commitment as a mediator in the influence of job satisfaction on employeesâ job performance in PT. Telkom KotabaruYogyakarta. A survey using questionnaire is conducted on 51 employees from each division. The evaluation of measurement is conducted to test the validity and the reliability of the questionnaire, and this found that there are 7 items that should be eliminated. To examine the role of affective commitment as mediator, Baron and Kennyâs (1986) mediation approach is utilized. The result shows that affective commitment mediates the influence of job satisfaction on job performance. After affective commitment is included in regression, the influence of job satisfaction on job performance decreases but is still significant (from Î²:0.452 to Î²: 0.327). These findings suggest that PT. Telkom Kotabaru Yogyakarta should concern not only job satisfaction but also affective commitment to improve job performance.